The Influence of Human Resource Quality on Organizational Commitment with Work Motivation as A Variable Intervening in BPJS Employment, Aceh Province - Andriani, Lidya; Farida Ferine, Kiki (Lafadz Jaya Publisher, 2023)
This research analyzes the influence of HR Quality on Organizational Commitment with Work Motivation as an intervening variable. This type of research can be classified as casual associative quantitative research. The population used was 108 employees and the sampling technique used was a saturated sampling technique because the researcher wanted to use the entire population as a sample. The data source used is a primary data source and the data collection carried out is distributing questionnaires and surveys. The research model used is Pahat analysis and the measuring instrument used is Smart PLS 3.3.3 The results of this research are as follows: for H1 Quality HR has a positive and significant effect as proven by the original sample value of 0.243 and p value 0.041 < 0.05. For H2 HR quality has a positive and significant effect on work motivation with the original sample value of 0.426 with p value 0.000 < 0.05. For H3 work motivation has a negative and significant effect towards Organizational Commitment with an original sample value of -0.479 with an ap value of 0.000 <0.05. Work Motivation is able to be a negative and significant intervening variable, which means that indirectly Work Motivation is able to influence HR Quality on Organizational Commitment but negatively as proven by the original sample results of -0.204 with ap value of 0.000.